Population genetics studies in Africa: curiosity and challenges - Soodyall, Himla (Henry Stewart Talks, 2007)
Use of genomic DNA to advance our knowledge and understanding of human evolution, biomedical research and mechanisms of disease, Acquiring specimens for research, Strict policies and recommendations guiding specimen acquirement, Social, ethical and legal issues when conducting research on human subjects, Factors to be considered when setting up qualitative and quantitative research, Case study: sub-Saharan Africa, in particular population genetics studies
Archived at 2018/10/28